Introduction: The Object in France Today - Martine Antle (Studies in 20th & 21st Century Literature, 1996)
Gilles Lipovetsky has aptly characterized the last two decades of the twentieth century as a period of ideologies crumbling into ethical ambiguity and contradictory values…
Keywords: France; 20th Century; Twentieth Century; modern